Determinants of Medication Nonadherence and Irregular Follow-Up Among Psychiatric Patients after Hospital Discharge in Qazvin, Iran (2024) - Hashemi, Seyedeh Zahra; Dodangeh, Samira; Mirzadeh, Monirsadat; Mohammadi, Zahra Sadat; Jafari, Pooria (Novelty in Biomedicine, 2026)
Background: Medication nonadherence in psychiatric patients can lead to symptom exacerbation, relapse, and prehospitalization. Regular follow-up visits with psychiatrists are also an important behavioral indicator of treatment adherence. This study aimed to evaluate the prevalence and factors associated with medication nonadherence and irregular visits to a psychiatrist among psychiatric patients after hospital discharge in Qazvin, Iran, in 2024. Materials and Methods: This prospective cohort study included all psychiatric patients admitted to the psychiatric clinic of Qazvin, Iran, during one month (23 August 2024 to 22 September 2024) using a census sampling method. Patients were followed by telephone at 6 and 12 months post-discharge to assess medication adherence and follow-up behaviors. Data were collected using a self-designed checklist covering demographic characteristics, psychiatrist visits, medication use, reasons for nonadherence, and relapse. Statistical analysis was performed using SPSS version 24, and associations were examined using Chi-Square Tests and t-tests, with significance set at p < 0.05. Results: A total of 97 patients were included (66 males, 68.0%). Forty-nine patients (61.9%) had irregular psychiatrist visits, and 21 (21.6%) did not use prescribed medications after discharge. The most common reason for avoiding psychiatrist visits was drug-related complications (38.1%). Irregular follow-up was significantly associated with a higher number of prior hospitalizations (p = 0.04), non-use of prescribed medications (p < 0.01), disease recurrence (p < 0.01), and readmission (p < 0.01). Conclusion: Both irregular psychiatrist visits and non-use of prescribed medications were common indicators of medication nonadherence among psychiatric patients after hospital discharge. Drug-related complications were the most frequently reported cause of poor adherence. Improving post-discharge monitoring, side-effect management, and patient education may enhance treatment adherence.